Back Cover: Dendrimeric nanosystem consistently circumvents heterogeneous drug response and resistance in pancreatic cancer (EXP2 1/2021). Issue 1 (1st September 2021) - Liu, Juan; Chen, Chao; Wei, Tuo; Gayet, Odile; Loncle, Céline; Borge, Laurence; Dusetti, Nelson; Ma, Xiaowei; Marson, Domenico; Laurini, Erik; Pricl, Sabrina; Gu, Zhongwei; et al.
Abstract : A fluorinated amphiphilic dendrimer based nanosystem to combat PDAC is reported by Juan Liu and co‐workers in the article number 20210003 .These nanoparticles markedly overcome the heterogeneity of drug response and resistance of primary tumor cells, constituting a promising drug delivery system for PDAC treatment.